AI and Spiritual Compatibility: Examining Human-Technology Interaction in Gen-Z Muslim Pilgrimage - Septyandi, Chandra Budhi; Utomo, Sherly Rakasiwi Putri (Politeknik Negeri Bandung, 2025)
This study investigates the adoption of artificial intelligence (AI) in domestic Islamic pilgrimage (ziarah) among urban Generation Z Muslims in Indonesia. Using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach, the study tests a conceptual model that incorporates perceived usefulness, AI-spiritual compatibility, trust in AI-generated religious content, perceived social norms, attitude, behavioral intention, and actual use behavior. Based on responses from 323 participants, the results indicate that attitude toward AI-assisted pilgrimage is the strongest predictor of both intention and actual usage. Perceived usefulness, trust, and social norms also significantly influence behavioral outcomes, while AI-spiritual compatibility exerts a weaker yet positive effect. These findings suggest that a combination of individual evaluation and socio-cultural context shapes the adoption of spiritual technology. The study contributes to the growing discourse on digital religion by demonstrating how AI can facilitate meaningful religious experiences. Implications for developers, religious leaders, and policymakers are discussed, along with directions for future research.